Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Komitmen Kerja Dengan Kepuasan Kerja Sebagai Variabel Mediasi Pada Karyawan AA Catering Cabang Padang Pada Masa Pandemi Covid 19 - Fidya Risyani; Rino Rino (Universitas Negeri Padang, 2023)
This research intends to analyze the extent to which the effects of compensation and the scope of work on employee activity commitments with activity happiness as intermediary elasticities. The population in this research is all employees of AA Catering Agent Padang, totaling 90 people as an illustration in this research. The analytical method used is SEM analysis using smart-PLS3. The results of this research prove that (1) compensation has an important effect on the activity commitment of AA Catering employees. (2) Compensation can have an important effect on the happiness of AA Catering employee activities. (3) Activity areas have an important influence on the activity commitment of AA Catering employees. (4) ) There is a direct and important and positive effect between the activity area and the happiness of the activity on AA Catering employees. (5) There is a direct and important and positive effect between the activity happiness and activity commitment on AA Catering employees. (6) There is an indirect and important and positive effect positive relationship between compensation and activity commitment through activity happiness for AA Catering employees. (7) There are indirect and important and positive effects between activity areas and activity commitment through activity happiness for AA Catering employees.